POTENSI INTEGRASI PRINSIP UTMOST GOOD FAITH DAN PRINSIP SHIDDIQ MENGGUNAKAN ARTIFICIAL INTELLIGENCE - Utomo, Damar Sugeng (JOURNAL EQUITABLE, 2025)
Utmost good faith principle in indonesia is often associated with good faith principle of the parties. In fact, good faith is an intention that is necessarily visible. Not only that, in Islam also known muamalah principle named shiddiq or honesty based on Quran. Both of this principle are often violated by insured which result in the cancellation of the insurance agreement. As one of many solution, insurance business actor can use artificial intelligence which able to process data more accurate and provide recommendations based on thousands or even millions of data available or provided as a source of processing. With the existence of such artificial intelligence, it is hoped to encourage the honesty of the insured parties so that sharia insurance contract are truly implemented based on consent of the parties, and still prioritize Islamic convey of truth, bot visible and what is not visible yet. This research examines the possibility of using artificial intelligence to check the honesty of the insured. This research was conducted using normative legal research methods. In this research, it was found that artificial intelligence can be used by insurance companies to get input so that they can measure the honesty and openness conveyed by the insured in sharia insurance, even though the final decision is still made by humans.